Factors Influencing the Successful Internship Program - Lee, Yet Yean (2010)
This research aims to determine the factors influencing successful internship program and it is significant to the private education institution chosen for this research as it measure how internship is able to groom students to its desired graduate attributes. In addition, it provides information to institutions, employers and students on the factors which have significant relationship to successful internship outcomes. This research is limited to engineering internship program in the chosen private education institution. Self-administered surveys were given to the students and from the data gathered, some of the results adhere to the past researchers analysis, some are totally new and a few actually contradicts the theories built by past researchers. This study concludes that internship program has a moderate success rate in achieving the desired graduate attributes of the institution under study. Among all attributes, the results show that “professionalism’’ is the most achievable attribute via internship. For factors influencing the success of internship program, 8 out of the 13 hypothesis made were found to have significant relationship in this study. They are worksite quality, internship placement process (proper guidance and perceived value of importance of internship), intern’s supervision and feedback (both host and internal supervisor), Intern characteristics (early perception towards internship, perceived value of importance of internship and age). On the other hand, the following shows no significant relationship towards internship program: academic preparedness, internship duration, gender, nationality and compensation.